A Monosaccharide Residue Is Sufficient to Maintain Mouse and Human IgG Subclass Activity and Directs IgG Effector Functions to Cellular Fc Receptors. - Kao, Daniela; Danzer, Heike; Collin, Mattias; Groß, Andrea; Eichler, Jutta; Stambuk, Jerko; Lauc, Gordan; Lux, Anja; Nimmerjahn, Falk (Cell Reports, 2015)
Immunoglobulin G (IgG) glycosylation modulates antibody activity and represents a major source of heterogeneity within antibody preparations. Depending on their glycosylation pattern, individual IgG glycovariants present in recombinant antibody preparations may trigger effects ranging from enhanced pro-inflammatory activity to increased anti-inflammatory activity. In contrast, reduction of IgG glycosylation beyond the central mannose core is generally believed to result in impaired IgG activity. However, this study reveals that a mono- or disaccharide structure consisting of one N-acetylglucosamine with or without a branching fucose residue is sufficient to retain the activity of the most active human and mouse IgG subclasses in vivo and further directs antibody activity to cellular Fcγ receptors. Notably, the activity of minimally glycosylated antibodies is not predicted by in vitro assays based on a monomeric antibody-Fcγ-receptor interaction analysis, whereas in vitro assay systems using immune complexes are more suitable to predict IgG activity in vivo.